Communication, Information, And Education (KIE) With Pocketbook Media To Increase Knowledge And Attitudes of Young Women About Reproductive Health As An Effort To Prevent Early Marriage - Nina Kholisna; Dhita Aulia Octaviani; Rafika Fajrin (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2023)
ABSTRACTEarly marriage is a marriage carried out by someone with an age limit between 10-19 years. Central Java is the eighth province with a fairly high early marriage rate of 8.71%. The health impacts that can result from early marriage are bleeding, prolonged labor, distortion, vesico-vaginal and recto-vascinal fistulas, preeclampsia, anemia, and stunting, post partum depression. The purpose of this study was to determine the effect of Communication, Information, and Education (IEC) using pocket books on increasing knowledge and attitudes of young women about reproductive health as a preventive measure for early marriage. The research was conducted at SMA N 1 Petungkriyono, Pekalongan Regency, with the type of pre-experimental research in the form of a One Group Pretest-Posttest Design. The research population is class X-XII students. The sampling technique used Stratified Random Sampling technique as many as 48 female students. The instrument used a questionnaire to measure the knowledge and attitudes of adolescents. The intervention was carried out by providing IEC through the media of a pocket book on reproductive health and early marriage. Statistical test results using the Wilcoxon Signed Rank Test on the knowledge variable obtained a p-value = 0.000 (0.05) meaning that there was a significant effect between before and after being given IEC with pocket book media and there was no effect on the attitude of young women before and after given IEC with pocket book media p-value = 0.095 ( 0.05). The results of this study are expected that female students can increase their knowledge by seeking more extensive and up-to-date information about reproductive health and early marriage and can participate in reducing the number of early marriages, especially in Pekalongan Regency.Â